1996
DOI: 10.1115/1.2836693
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Low Aspect Ratio Transonic Compressor Stage Using CFD Techniques

Abstract: A transonic compressor stage has been designed for the Naval Postgraduate School Turbopropulsion Laboratory. The design relied heavily on CFD techniques while minimizing conventional empirical design methods. The low aspect ratio (1.2) rotor has been designed for a specific head ratio of 0.25 and a tip relative inlet Mach number of 1.3. Overall stage pressure ratio is 1.56. The rotor was designed using an Euler code augmented by a distributed body force model to account for viscous effects. This provided a rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…In these figures, the circles are the blade coordinates and the lines are the fitted Bezier curves. Then, using surface fitting, the pressure and suction surfaces of the baseline transonic rotor blade used in the present study (Sanger, 1996) were found to be represented to well-within the tolerances called for in manufacture (0.1 mm for a rotor diameter of 27.94 cm). The remaining problem was to represent the leading and trailing edges using Bezier patches.…”
Section: F]mentioning
confidence: 66%
See 3 more Smart Citations
“…In these figures, the circles are the blade coordinates and the lines are the fitted Bezier curves. Then, using surface fitting, the pressure and suction surfaces of the baseline transonic rotor blade used in the present study (Sanger, 1996) were found to be represented to well-within the tolerances called for in manufacture (0.1 mm for a rotor diameter of 27.94 cm). The remaining problem was to represent the leading and trailing edges using Bezier patches.…”
Section: F]mentioning
confidence: 66%
“…The geometry package was used to generate and analyze the flow through a baseline rotor and swept geometries using CFD. The baseline geometry used was the transonic rotor designed by Sanger (1996). The Sanger rotor coordinates were read by the geometry package in MERIDL3 format and fitted with Bezier surfaces.…”
Section: Application To Sweepmentioning
confidence: 99%
See 2 more Smart Citations
“…2. Rotor (a)'s geometry and its design by Sanger [9] was published in open literature. Rotor (b) was a more advanced proprietary design, which included forward sweep.…”
Section: Introductionmentioning
confidence: 99%